Furosemide self nano emulsifying drug delivery system (SNEDDS) formulation comprising of capryol-90, polysorbate-80, and peg-400 with simplex-lattice-design - Najma Annuria Fithri; Mardiyanto Mardiyanto; Rennie Puspa Novita; Vicky Andrean (Science and Technology Indonesia, 2017)
Preparation of SNEDDS aims to improve solubility and absorption of furosemide in the body to reduce the dosage and minimize the side effects of drugs. Ternary diagram constructed from composition mixture produced nanoemulsion in the range of 20-40% of capryol-90, 20-40% polysorbate-80 and 40-60% PEG-400. Formulations of SNEDDS using Design-Expert®10 with simplex-lattice-design method in the study was aimed to investigate the effect of SNEDDS each component's proportions towards test responses. Emulsification time, drug content and viscosity were best demonstrated by run-7 with consecutive values of 131.68±2.14 seconds, 99.89±2.68% and 0.87±0.0043 mm2/s. The optimum formula was obtained through entering test response parameter data of all thirteen formula. Drug content and emulsification time was 107.0 ± 1.44% and 155.59±1.56 seconds with viscosity value 0.91±0.00 mm2/s. From the physical stability studies, SNEDDS formulas were stable and did not show phase separation when exposed to temparature stress testing.